The Effect of Parents Assistance on Creativity Student Class II SD Negeri 054931Batu Malenggang - Ayu Sahprida (Berpusi Publishing, 2023)
This study consisted of two variables, namely parental assistance as the independent variable (X) and creativity as the dependent variable (Y). This study aims to determine the Effect of Parental Assistance on the Creativity of Grade II Students at SD N 054931 Batu Melenggang. This type of research is quantitative research. The population of this study were all 25 grade II students at SD N 054931 Batu Melenggang. The sampling technique used is saturated sampling where all members of the population are used as samples. Data collection techniques using a questionnaire. Based on the research results Description si the results of this study to know the description of each research variable presented with descriptive statistics. The answers that the respondents gave will be described in the form of minimum, maximum, average and standard deviation values . Based on research results And the discussion that the researcher did obtained the results of the t test with SPSS 20. with significant value 0.000 < 0.05 with t- count of 1,928 where more big from the t- table that is 1.7108. Then this shows that the hypothesis Ho is rejected and Ha is accepted . Which means accompaniment Parent influential positive And significant to Creativity Student Class II SD N 053941 Batu Melenggang.